2016
DOI: 10.1002/ajmg.a.37985
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic hypocellularity, blastogenetic malformations, and fetal growth restriction

Abstract: An association between congenital malformations and fetal growth restriction (FGR) can be largely explained by a relationship with early embryonic hypocellularity. The malformations include the VACTERL association, which is exceptional as a Mendelian syndrome, but is commonly associated with monozygotic twinning, maternal diabetes, and some forms of aneuploidy, all characterized by a small embryo early in development. Parsimony suggests that these different links to VACTERL are related to the hypocellularity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 73 publications
(91 reference statements)
1
20
0
Order By: Relevance
“…Late secondtrimester miscarriages with malformations also occurred about 3 weeks before those without [58]. For typically euploid sirenomelia, 47% of cases were liveborn, 71.2% premature, and 88.2% at under 2500 g, while 8% of informative cases were from multiple gestations, and 5% had diabetic mothers [61], consistent with involvement of the early hypocellularity that is a risk factor for VACTERL [4].…”
Section: Vacterl and Adverse Outcomesmentioning
confidence: 87%
See 2 more Smart Citations
“…Late secondtrimester miscarriages with malformations also occurred about 3 weeks before those without [58]. For typically euploid sirenomelia, 47% of cases were liveborn, 71.2% premature, and 88.2% at under 2500 g, while 8% of informative cases were from multiple gestations, and 5% had diabetic mothers [61], consistent with involvement of the early hypocellularity that is a risk factor for VACTERL [4].…”
Section: Vacterl and Adverse Outcomesmentioning
confidence: 87%
“…The atresia probably reflects an early hypocellularity, as seen with conditions such as monozygotic twinning and maternal diabetes. This reduction, although not a direct cause for anomalies, is a predisposition to IBMs [4], and is a likely risk factor for other adverse pregnancy outcomes.…”
Section: Single Umbilical Arterymentioning
confidence: 90%
See 1 more Smart Citation
“…A possible explanation is that the suboptimal condition of the fetus induced compensatory placental enlargement and a predisposition to preterm birth. Some congenital malformations including those with VACTERL association showed severe fetal growth restriction due to somatic hypocellularity [ 18 ]. In our study, a low BW/PW ratio was identified within the major anomaly subgroups of other anomalies/syndromes and chromosomal abnormality, which may be caused by fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that fetal growth restriction was associated with chromosomal abnormality [ 19 ], VACTERL association [ 18 ], congenital heart defects [ 20 ], anencephaly [ 13 ], gastroschisis [ 13 ], esophageal atresia [ 13 ], and renal aplasia [ 13 ]. However, the association between congenital anomalies and the BW/PW ratio remains unknown.…”
Section: Discussionmentioning
confidence: 99%